2001
DOI: 10.1357/002224001762882673
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Makassar Strait

Abstract: Data collected as part of the Arlindo Project ("Arlindo" is an acronym for Arus Lintas Indonesia, meaning "through ow" in Bahasa Indonesia) from October 1996 to March 1998 are analyzed to study the characteristics of the ow through the Makassar Strait. Analysis of inverted echo sounders (IES) and bottom pressure data (PIES) combined with TOPEX/POSEIDON satellite-derived sea height anomaly suggest that a minimum of three-layer approximation is necessary to explain the dynamics of the ow in the Makassar Strait. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…From analyses of measurements in the Makassar Strait, Waworuntu et al [2001] concluded that a model of at least three layers is required to appropriately describe the Makassar Strait throughflow, which is consistent with our findings, where the bulk of this throughflow occurs in and is limited to the thermocline.…”
Section: Model Experiments: Barotropic Mode and No Local Windsupporting
confidence: 88%
“…From analyses of measurements in the Makassar Strait, Waworuntu et al [2001] concluded that a model of at least three layers is required to appropriately describe the Makassar Strait throughflow, which is consistent with our findings, where the bulk of this throughflow occurs in and is limited to the thermocline.…”
Section: Model Experiments: Barotropic Mode and No Local Windsupporting
confidence: 88%
“…Hal ini dikarenakan kedalaman 20-50 m merupakan lapisan homogen (Ilahude, 1979). Homogenitas tersebut menunjukkan nilai Suhu di perairan Laut Jawa memiliki nilai yang sama hingga kedalaman 50 m. Suhu di Laut Jawa juga mendapat pengaruh dari Arlindo yang membawa air hangat dari Selat Makassar dengan skala yang besar (Waworuntu et al, 2001). Pengaruh Arlindo ini ditunjukkan oleh adanya wilayah perairan panas pada saat periode Monsun Barat di Laut Jawa bagian Timur.…”
Section: Pengaruh Arlindo Terhadap Suhuunclassified
“…The moorings included temperature and temperature-pressure sensors. In addition, in close proximity to the moorings, there were pressure-inverted echo sounders (PIES) [Waworuntu et al, 2001]. In anticipation of mooring blowover, the ADCPs were set in the ''surface tracking'' mode and data can be corrected for the vertical oscillation; bin 1 is the closest to the ADCP sensor at 140 m depth while bin 25 is set at 52 m above the surface (8-m-depth bin increment).…”
Section: Introductionmentioning
confidence: 99%